Optimizing processing methods for maximum bioactive retention: comparative metabolomic analysis of dried loquat (Eriobotrya japonica) flowers and their powdered extracts - Duan, Mingzheng; Feng, Jieming; Feng, Jing-Han; Wang, Xi; Xiao, Xu; He, Shirong; Guo, Hengcui; Zhang, Wenyan; Jiang, Zhumao; Wan, Tongfa; Rao, Muhammad Junaid (Frontiers in Nutrition, 2025)
Loquat (Eriobotrya japonica) flowers are a rich source of bioactive flavonoids, but their nutraceutical potential depends on post-harvest processing. This study evaluated the impact of heat-drying (HD) and freeze-drying (FD) on flavonoid retention in loquat flowers and their hot-water powdered extracts using UPLC–MS/MS metabolomics and antioxidant assays. Freeze-drying significantly preserved thermolabile compounds, with cyanidin showing a 6.62-fold increase (Log2FC 2.73) in FD compared to HD, while delphinidin 3-O-beta-D-sambubioside surged 49.85-fold (Log2FC 5.64). In contrast, heat-drying degraded many flavonoids but selectively enhanced others, such as 6-hydroxyluteolin (27.36-fold increase, Log2FC 4.77), and methyl hesperidin showed highlest percentage abundance (10.03%). Freeze-dried powder (FDP) exhibited the highest antioxidant activity (608.83 μg TE/g), linked to elevated levels of key metabolites like eriodictyol chalcone (18.62-fold increase, Log2FC 4.22). Multivariate analyses confirmed distinct clustering, with FD samples closely grouped, indicating stable metabolite preservation. Heat-dried samples showed greater variability, reflecting thermal degradation and pathway activation. The results demonstrate that freeze-drying optimizes flavonoid retention, making it ideal for high-quality nutraceuticals, while heat-drying may suit cost-effective production of select heat-stable compounds. These insights guide the development of standardized loquat flower products, balancing bioactive preservation with processing efficiency for functional food and herbal medicine applications.